IMPLEMENTASI MODEL BUSINESS TO BUSINESS PADA PEMASARAN PRODUK JAMU MENGGUNAKAN FRAMEWORK LARAVEL - Dwi Wahyuda, Arya; Sembiring , Boni Oktaviana; Aulia Rahmah, Sabrina (P3M STMIK Profesional Makassar, 2025)
The advancement of digital technology presents great opportunities for business actors to enhance their competitiveness through more efficient marketing strategies. This study aims to implement the Business to Business (B2B) model in the marketing of traditional herbal products by Jamu Dapoer Niswah using the Laravel Framework and the Agile method. The system developed is a web-based platform with core features such as business partner registration, product catalog, ordering, order tracking, and contract management. The Agile method was chosen for its flexibility in responding to changing user needs through iterative development. This study adopts an iterative approach consisting of planning, implementation, testing, documentation, deployment, and maintenance stages. The implementation results show that the system is capable of accelerating the ordering process, improving transaction accuracy, and expanding the partner market reach. System testing was conducted using the black-box method and showed that all features function as intended. With this system, the marketing and distribution processes of herbal products can be carried out in a more structured and efficient manner, accessible to business partners at any time. This system is expected to become a digital solution that supports B2B marketing transformation in the traditional business sector.